Current Distribution of Golden Potato Cyst Nematode, Globodera rostochiensis (Tylenchida, Heteroderidae), in Ukraine - Borzykh, O. I.; D. D. Sigareva; O. L. Fedorenko; T. I. Bondar; V. V. Kornyushin; O. O. Sokolova; V. G. Karpliuk (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
Globodera infestation was evaluated in soils of private farm plots in Chernihiv and Kyiv regions of Ukraine in 2017-2018. Soil samples were taken at 88 farms, 15.02 ha in total, in 11 settlements of 6 districts. The nematode abundance in the examined areas was graded as follows: less than 1000 eggs+larvae/100 cm3 — low rate of infestation; 1000–5000 eggs+larvae/100 cm3 — average rate; more than 5000 eggs+larvae/100 cm3 — high rate. 85.4% of study area is infested with the golden potato cyst nematode. The mean abundance of pest was 3331 (15-23237) eggs+larvae/100 cm3: 8730 (91-21486) eggs+larvae/100 cm3 in Kyiv region and 1829.6 (15-23237) eggs+larvae/100 cm3 in Chernihiv region. The highest number of assessed plots per district (29) was in Koryukivsky district, and the mean abundance of G. rostochiensis (Rо-1) was 1549 (20-15757) eggs+larvae/100 cm3 e+l/100cm3. We also analyzed the results of golden nematode monitoring conducted by the State Service of Ukraine for food safety and consumer protection in 2018. According to those, the golden nematode is found in 18 regions of Ukraine. In most of those (14 regions), the pest infests rather small areas, less than 500 ha. Globodera is not recorded in the other 7 regions of Ukraine and Autonomous Republic of Crimea for now.